Evaluation and selection of video stabilization techniques for UAV-based active infrared thermography application - Pant, Shashank; Nooralishahi, Parham; Avdelidis, Nicolas P.; Ibarra-Castanedo, Clemente; Genest, Marc; Deane, Shakeb; Valdes, Julio J.; Zolotas, Argyrios; Maldague, Xavier P. (MDPI, 2021)
nmanned Aerial Vehicles (UAVs) that can fly around an aircraft carrying several sensors, e.g., thermal and optical cameras, to inspect the parts of interest without removing them can have significant impact in reducing inspection time and cost. One of the main challenges in the UAV based active InfraRed Thermography (IRT) inspection is the UAV’s unexpected motions. Since active thermography is mainly concerned with the analysis of thermal sequences, unexpected motions can disturb the thermal profiling and cause data misinterpretation especially for providing an automated process pipeline of such inspections. Additionally, in the scenarios where post-analysis is intended to be applied by an inspector, the UAV’s unexpected motions can increase the risk of human error, data misinterpretation, and incorrect characterization of possible defects. Therefore, post-processing is required to minimize/eliminate such undesired motions using digital video stabilization techniques. There are number of video stabilization algorithms that are readily available; however, selecting the best suited one is also challenging. Therefore, this paper evaluates video stabilization algorithms to minimize/mitigate undesired UAV motion and proposes a simple method to find the best suited stabilization algorithm as a fundamental first step towards a fully operational UAV-IRT inspection system.
Keywords: active infrared thermography; unmanned aerial vehicle (UAV); composites; aerospace components; video stabilization